Clinical Decision Making Using CTA in Conjoined, Bipedicled DIEP and SIEA for Unilateral Breast Reconstruction - Cho, Min-Jeong; Haddock, Nicholas T.; Teotia, Sumeet S. (Journal of Reconstructive Microsurgery, 2020)
Background Using a hemi-abdominal flap for unilateral breast reconstruction in patients may not be ideal due to paucity of abdominal tissue, presence of a lower abdominal midline scar, or a larger and/or ptotic contralateral native breast. Several algorithms exist to make these flaps successful, but all of them require an anastomosis sequence ultimately. In this study, we present our experience with the use of imaging to predict flap dominance and anastomosis sequence to make them consistently successful.Methods Seventy-five consecutive conjoined, bipedicled abdominal composite free flaps for unilateral breast reconstruction were performed. Preoperative computed tomographic angiography (CTA) was obtained to depict the pattern of perforators, flap dominance, and feasibility for intraflap anastomosis. Patient demographics, type/weights of flaps, number of anastomoses, location of perforators, length/type of pedicles, and flap-related complications were reviewed.Results Seventy-five patients underwent composite deep inferior epigastric perforator (DIEP) and/or superficial inferior epigastric artery (SIEA) flaps. There were 62 DIEP-DIEP flaps, 11 DIEP-SIEA flaps, and two SIEA-SIEA flaps. The mean age was 57 years with an average body mass index of 27 kg/m2 and flap weight of 1,054 g. Thirty-one patients underwent intraflap (41%) and 44 patients underwent crania/caudal anastomoses (59%). In comparison to bilateral DIEPs, the total number of perforators was significantly lower (2.9 vs. 3.8), and fat necrosis rate was lower (2.7 vs. 14.4%) as well.Conclusion Guided by preoperative CTA imaging, we recommend the consistent use of these conjoined, bipedicled hemi-abdominal flaps for unilateral breast reconstruction, primarily those with delayed reconstruction and radiation deficits. Preoperative CTA imaging is crucial in directing perforator dissection to maximize overlapping perfusion zones and guide in performing anastomoses.
Keywords: computed tomographic angiography; DIEP flaps; SIEA flaps; breast reconstruction; decision making